2016
DOI: 10.1590/1516-3180.2015.00100108
|View full text |Cite
|
Sign up to set email alerts
|

Script concordance test in medical schools in Brazil: possibilities and limitations

Abstract: CONTEXT AND OBJECTIVE: Routine use of the script concordance test (SCT) is not common in Brazilian universities. This study aimed to analyze application of the SCT in the medical school of a Brazilian university. DESIGN AND SETTING: Quantitative, analytical and descriptive study in the medical school of a Brazilian university. METHODS: A total of 159/550 students participated. The test comprised ten clinical cases within internal medicine, with five items per case, rated on a five-point Likert scale. The test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
1
5
0
2
Order By: Relevance
“…Another possible explanation is the students training and familiarity with the test format. This point met agreement with Roberti et al [25] who suggested that the SCT di culties in construction of the test and scoring key might make its application unfeasible in units with limited resources [25,26]. Also, Lineberry et al 2019 [26] reported that SCT can be used as a guide for assessment for learning.…”
Section: Discussionsupporting
confidence: 76%
“…Another possible explanation is the students training and familiarity with the test format. This point met agreement with Roberti et al [25] who suggested that the SCT di culties in construction of the test and scoring key might make its application unfeasible in units with limited resources [25,26]. Also, Lineberry et al 2019 [26] reported that SCT can be used as a guide for assessment for learning.…”
Section: Discussionsupporting
confidence: 76%
“…A study from Brazil has shown progression of SCT scores from students in the pre-clinical phase to those in the clinical phase (51.6% to 63.4%) using 10 clinical cases. However, the authors concluded that the implementation of this exam format is difficult in under-resourced institutions and have not followed up on these findings 28 …”
Section: Discussionmentioning
confidence: 99%
“…19 The SCT has been introduced and evaluated in the medicine curricula to assess clinical reasoning for topics in undergraduate and postgraduate didactic and clinical education. [20][21][22][23][24][25][26][27][28][29][30][31] The SCT template has also been used to develop other assessment tools such as the ethics SCT to assess reasoning abilities on ethical dilemmas in high-cognitive level 28,29 or the evolving SCT where, as new information is presented at each stage, the clinical decision-making becomes increasingly clear. 22 The SCT has been combined with other clinical reasoning assessments such as the think aloud to enhance the assessment by allowing the examinees to provide justification for their responses that would have been considered incorrect and identify questions that are frequently misinterpreted.…”
Section: Introductionmentioning
confidence: 99%